Investigation on Shear Wave Velocity and Triaxial Mechanical Performance of Tailings Core from Tailings Dam - Pengfei Luo (Advances in Civil Engineering)
The physical and mechanical parameters of tailings are important to study the stability of tailings dams (TDs). In this study, a series of laboratory experiments (shear wave velocity, triaxial compressive, and peak strain strength testing) were conducted to obtain the mechanical properties of tailings from TD. The results showed the following. (1) The linear function fitting could characterize the quantitative relationship between shear wave velocity and hole depth. (2) The corresponding static pressure coefficient increased as the confining pressure increased. The exponential fitting could characterize the quantitative function relation between the static pressure coefficient and the confining pressure. (3) The cohesion and internal friction angle of the tailings sample were 20 kPa and 41°, respectively, and the logarithmic fitting could better characterize the quantitative relation between shear peak strength and confining pressure. The results of this study can provide important references for further research on the stability of TD.